Evaluating autologous peritoneum grafting for enhanced healing of bile duct injuries: A preliminary data from an animal study - Nugroho, Anung N.; Mudigdo, Ambar; Soetrisno, Soetrisno; Yarso, Kristanto Y.; Nurwati, Ida; Indarto, Dono; Pamungkasari, Eti P. (Narra Sains Indonesia, 2025)
Increased incidence of laparoscopic cholecystectomy-related bile duct injuries (BDIs), combined with its risk of serious complications and mortality, highlights the need for a more effective repair technique. Although the use of autologous graft in BDI repair has been promoted, the role of autologous parietal peritoneum remains underexplored. The aim of this study was to evaluate the effect of autologous parietal peritoneum grafts in rabbit models of partial BDI, emphasizing its effect on the expression of cluster of differentiation 68 (CD68) and transforming growth factor-β (TGF-β). An experimental post-test-only design was employed, using 27 male New Zealand rabbits (Oryctolagus cuniculus) aged 8–10 months. The rabbits were allocated into three groups: control (primary closure), autologous parietal peritoneum graft, and autologous gallbladder graft. Partial BDI measuring 15×5 mm were surgically created and repaired according to group assignments. The expression of CD68 and TGF-β were measured via enzyme-linked immunosorbent assay (ELISA), while the anastomosis was pathologically examined through hematoxylin and eosin (H&E) staining on days 3, 7, and 14 post-surgery. Statistical analysis was performed using analysis of variance (ANOVA) followed by Bonferroni post hoc tests. No statistically significant difference was observed in the expression of CD68 or TGF-β among the three treatment groups on days 3, 7, and 14 post-surgery, indicating that the effects of autologous parietal peritoneum graft were comparable to the control and the autologous gallbladder graft in promoting wound healing. Fibroblast density on day 3 was significantly lower in the parietal peritoneum group (p=0.040), reflecting delayed recruitment, but normalized by day 14, indicating successful integration and remodeling. The study highlights the potential role of autologous parietal peritoneum grafts for BDI.